FACTORS ASSOCIATED WITH PATIENT UNDERSTANDING OF PHYSIOTHERAPY SERVICE FLOW: A CROSS-SECTIONAL STUDY BASED ON PERMENKES NO. 65 OF 2015 - Balqis Wasliati; Nadia Wasliati; Laily Wasliati (Pena Cendekia Insani, 2026)
Patient understanding of physiotherapy service flow is essential for adherence and outcomes. This study analyzes factors associated with patients' understanding based on Minister of Health Regulation No. 65/2015 at BLU Timikan Hospital. A cross-sectional study was conducted among 158 outpatients selected by consecutive sampling at BLU Timikan Hospital from January to March 2025. Data were collected using observation sheets, a validated questionnaire (Cronbach's alpha = 0.87), and medical records. Bivariate analysis employed chi-square tests, and multivariate analysis used logistic regression to calculate adjusted odds ratios (AOR) with 95% confidence intervals (CI), controlling for age and education. Complete implementation was lowest for periodic evaluation (41.8%) and discharge planning (36.7%). Overall, 45.8% of patients demonstrated good understanding, with the poorest comprehension observed for informed consent (27.8%) and follow-up plans (25.3%). Bivariate analysis showed that incomplete flow implementation (chi^2 = 7.34, p = 0.007, phi = 0.215), verbal-only education (chi^2 = 10.82, p = 0.001, phi = 0.262), and lack of family support (chi^2 = 8.71, p = 0.003, phi = 0.235) were significantly associated with poor understanding, whereas waiting time was not (p = 0.218). After controlling for age and education, incomplete flow implementation (AOR = 2.84; 95% CI: 1.42-5.68; p = 0.003) and verbal-only education (AOR = 2.93; 95% CI: 1.44-5.96; p = 0.003) remained independently associated with poor understanding. The model demonstrated adequate fit (Hosmer Lemeshow p = 0.612).